2003
DOI: 10.1095/biolreprod.102.005082
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Sperm Capacitation and Tyrosine Kinase Activity Are Dependent on Bicarbonate and Calcium but Protein Tyrosine Phosphorylation Is Only Associated with Calcium1

Abstract: Mammalian sperm undergo capacitation in the female reproductive tract or under defined conditions in vitro. Although capacitation is now considered to be mediated by intracellular signaling events, including protein phosphorylation, the regulation of the transduction mechanisms is poorly understood. The objective of the present study was to evaluate the importance of medium components on capacitation of porcine sperm, the appearance of an M(r) 32 000 sperm protein (p32), and activity of a tyrosine kinase (TK-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 61 publications
9
62
1
1
Order By: Relevance
“…Consistent with other studies, we have demonstrated increases in protein tyrosine phosphorylation in both incubated and cooled sperm, including an increase in the phosphorylation of a 32-kd protein band (Green et al, 2001;Kaneto et al, 2002;Tardif et al, 2003;Bravo et al, 2005). This 32-kd protein has recently been identified as proacrosin-binding protein, and its phosphorylation has been clearly shown to be associated with capacitation (Dube et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with other studies, we have demonstrated increases in protein tyrosine phosphorylation in both incubated and cooled sperm, including an increase in the phosphorylation of a 32-kd protein band (Green et al, 2001;Kaneto et al, 2002;Tardif et al, 2003;Bravo et al, 2005). This 32-kd protein has recently been identified as proacrosin-binding protein, and its phosphorylation has been clearly shown to be associated with capacitation (Dube et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Sp32 was highly expressed in capacitated sperm or during prophase in the acrosomal reaction. This observation fits the expectation that sp32 is a special protein participating in sperm capacitation (Tardif et al, 2003), suggesting that the expression level of sp32 regulates acrosomal protein activation. Frozen-thawed sperms also displayed clear sp32 bands but had lower amounts of sp32 compared to those of capacitated sperms or during prophase of the acrosomal reaction.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that P32 is phosphorylated sp32, and the phosphorylation accompanies boar sperm capacitation. In addition, sp32 plays an important role in the maturation of acrosin (Tardif et al, 2003). Therefore, sp32 is involved in capacitation through tyrosine phosphorylation and binds with proacrosin.…”
Section: Introductionmentioning
confidence: 99%
“…Incubation of murine spermatozoa in media devoid of bicarbonate, calcium, or albumin prevents capacitation as assessed by the ability of these spermatozoa to undergo a zona pellucidainduced acrosome reaction and fertilize oocytes in vitro [Visconti et al 1995]. Similarly, porcine spermatozoa capacitation is dependent upon calcium and bicarbonate, but does not appear to require albumin, possibly due to the remarkably low cholesterol: phospholipid ratio of porcine spermatozoa [Althouse 1992;Tardif et al 2003]. However, porcine spermatozoa capacitation can be inhibited by an increase in membrane cholesterol mediated by cyclodextrin (Galantino-Homer et al 2006).…”
Section: Sperm Capacitationmentioning
confidence: 99%
“…After 2 hours of incubation in a capacitation-supporting environment, the concentration of intracellular calcium increased from 70 to 250 nM in human spermatozoa [Baldi et al 1991]. Similarly, bovine and porcine sperm capacitation have been shown to be calcium-dependent and associated with increases in intracellular calcium [Handrow et al 1989;Tardif et al 2003]. Voltage-gated calcium channels, calciumATPase inactivation, and the sodium-calcium pump have been postulated to result in this calcium influx [Florman et al 1992].…”
Section: Role Of Calcium In Capacitationmentioning
confidence: 99%